CHARACTERISATION OF CEILING BOARDS PRODUCED FROM PLASTER OF PARIS REINFORCED WITH BANANA FIBRE AND COCONUT SHELL - Eugenia Obidiegwu; Munirat Ayomide BALOGUN; Paul Adedeji AJAYI (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ)
The need for environmentally friendly and affordable building materials has sparked researches for materials to use in the construction industry. This paper therefore, studied the characterization of ceiling boards manufactured from plaster of Paris (POP) reinforced with banana fibres (BF) and coconut shell (CS) particulates. The samples were produced by adding different ratios of BF and CS to the POP matrix. To evaluate the effectiveness of the samples, several tests, were conducted. The results demonstrated that the addition of reinforcements improved the properties. The sample with a mixture of POP, BF, and CS demonstrated superior properties with the lowest water absorption (2.77%), high compressive strength (7.74 MPa), least thermal conductivity (0.2157 kW/mK) and hardness value of (23.2 HVN), these are within the standard range. The Scanning Electron Microscopy (SEM) analysis confirmed the results obtained. This study established the possibility of using local accessible materials to produce high quality ceiling boards.